Comparison of Sonographically Evaluated Pre and Postprandial Gastric Antral Area in Type 2 Diabetics and Healthy Control Subjects (BIRDEM Medical Journal, 2016)
Background: Gastric motility associated with delayed gastric emptying occurs frequently in patients with diabetes mellitus. Ultrasonography play an important role by which the structure and function of the stomach can be assessed in an accurate and reproducible manner. Ultrasonographic measurement of antral cross sectional area provides a valid, cheap alternative to other costly modalities for early measurement of gastric emptying . Increased gastric antral area reflects delayed gastric emptying and gastroparesis in type 2 diabetic. Post prandial antral area is also increased in healthy subjects. But there is a significant difference in sonographically measured postprandial gastric antral area in type 2 diabetics and healthy control subjects. No such study was done previously with Bangladeshi diabetic subjects.Aims & Objective: This study was performed to compare pre and postprandial gastric antral area in type 2 diabetics and in healthy controls by ultrasonography in Bangladeshi subjects.Materials and methods: A total number of 45 consecutive type 2 diabetic subjects referred in the Department of Radiology and Imaging, BIRDEM, Dhaka, for ultrasonography of whole abdomen as routine checkup and 45 healthy subjects who underwent ultrasonography for whole abdomen for the period of one year, were enrolled in this study and were considered as group I and group II respectively. Smokers, snuff users, patients with connective tissue, cerebrovascular & endocrine diseases, receiving any drug affecting gastrointestinal motility, any previous gastriontestional tract surgery except appendisectomy were excluded from the study. All the selected subjects underwent B mode ultrasonogram of whole abdomen before and 90 mins after solid breakfast (two slices of bread and an egg). Unpaired t-test was done to compare pre and postprandial gastric antral area between type 2 diabetics and healthy controls and a P value